IMPLEMENTING THE USE OF SIX SIGMA FOR QUALITY AND CONTINUOUS IMPROVEMENT - Musah, Issah (My University, 2017)
This thesis investigates the how Six Sigma can be applied to aid to trace the root cause of why the organization under study is not seeing much progress, to find out how to improve the quality of service and also aid in the continuous improvement of the organization. The theoretical framework employed is the Lean Six Sigma (LSS) which deploy the general concept of eliminating waste in any given system or service to promote efficiency through careful usage of the five phases of Six Sigma. The study deploys the use of a qualitative research and data was gathered by submitting questionnaires to the employees of the organization. After a careful analysis of the data by the deployment of the phases of Six Sigma (DMAIC), suggestions and proposals are given for factors that need improvement through management initiative and direction. The overall idea of the thesis was to implement the use of Six Sigma for quality and continuous improvement. The writer hopes that by implementing these proposals of the study, there would be a significant improvement in the quality of services provided and a significant progress would be seen in the organization.
Keywords: Total quality management; continuous improvement; quality improvement; Six Sigma; Lean Six Sigma.; fi=Tuotantotalous|en=Industrial Management|; fi=Master's Degree Programme in Industrial Management|